Salivary Human β-Defensin 1-3 and Human α-Defensin-1 Levels in Relation to the Extent of Periodontal Disease and Tooth Loss in the Elderly - Gürsoy Ulvi Kahraman; Gürsoy Mervi; Liukkonen Anna; Suominen Anna Liisa; Könönen Eija (Switzerland, 2025)
The oral innate immune response may diminish with aging. In the present study, the aim was to examine human β-defensin (hBD) 1-3 and human neutrophil peptide (HNP)-1 levels in the saliva of an elderly population to establish the extent of periodontal disease and tooth loss. A total of 175 individuals aged ≥ 65 years were divided into five groups based on the number of teeth with a pocket depth ≥ 4 mm as follows: 17 pocket-free individuals (Control), 55 individuals having 1-6 pocket teeth (PerioA), 33 individuals having 7-13 pocket teeth (PerioB), 29 individuals having at least 14 pocket teeth (PerioC), and 41 edentulous individuals. Their salivary defensin levels were measured with ELISA kits. The salivary HNP-1 levels were significantly higher in the Perio groups (PerioB: p < 0.001 and PerioC: p < 0.001) in comparison to the Control. The associations between salivary HNP-1 levels and the number of pocket teeth remained significant after adjustments for age, gender, level of education, and number of teeth. The salivary HNP and hBD levels differed in terms of their correlation to the extent of periodontal disease and tooth loss in the elderly.